Strategi Penyusunan Program Tahunan dan Semesteran BK untuk Meningkatkan Kualitas Layanan Bimbingan di Sekolah - Ardianti, Ni Kadek Yuanita Adriana; Faradila, Ismi; Eraeni, St.; Malaghah, Nawaf Nur Nejwa Muhsin; Andani, Novia Fitri (Lembaga Yasin AlSys, 2025)
The importance of developing annual and semester programs in Guidance and Counseling (BK) at schools is the primary focus of this article, which aims to enhance the quality of counseling services. This research intends to provide practical guidelines for BK teachers in designing effective programs that are responsive to students' needs. The methodology employed in this study is qualitative, utilizing a literature review approach that involves collecting data from various relevant sources. The findings indicate that a well-structured BK program can optimize services, increase student participation, and address various challenges in program implementation. A well-designed program should include the identification of student needs, the establishment of clear objectives, and periodic evaluations to ensure the relevance and effectiveness of services. Thus, this article emphasizes the significance of structured planning in improving the quality of BK services in schools.